2001
DOI: 10.1038/sj.ijo.0801808
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum interleukin-6 concentrations in obese children and adolescents during a weight reduction program

Abstract: OBJECTIVE:To investigate the effect of short term energy restriction combined with physical activity on serum concentrations of Interleukin-6 (IL-6) in obese children and adolescents. DESIGN: Longitudinal intervention study of 3.8 -5 MJ daily with exercise. SUBJECTS: Forty-nine white obese children and adolescents (31 girls, age 11.9 AE 1.8 y; 18 boys, age 11.6 AE 1.7 y). MEASUREMENTS: Indexes of obesity, IL-6, leptin, estradiol, systolic and diastolic blood pressure, heart rate at baseline and after 3 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
3
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 28 publications
5
58
3
6
Order By: Relevance
“…The level of obesity may therefore explain the missing acute reduction in IL-6, fibrinogen and partly hs-CRP, as the present participants were not morbidly obese and had no evidence of metabolic or systemic diseases. However, other studies with similar subject groups have observed significant acute reductions in hs-CRP, 15,[17][18][19][38][39][40] 15,17,39,[41][42][43] and fibrinogen 23,30,[44][45][46] at smaller and similar weight losses (4-20 kg). One explanation could be that the present study was underpowered to detect a significant change in the pro-inflammatory markers after weight reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of obesity may therefore explain the missing acute reduction in IL-6, fibrinogen and partly hs-CRP, as the present participants were not morbidly obese and had no evidence of metabolic or systemic diseases. However, other studies with similar subject groups have observed significant acute reductions in hs-CRP, 15,[17][18][19][38][39][40] 15,17,39,[41][42][43] and fibrinogen 23,30,[44][45][46] at smaller and similar weight losses (4-20 kg). One explanation could be that the present study was underpowered to detect a significant change in the pro-inflammatory markers after weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis is not fully developed and cannot explain why the present findings diverge from those found in three similar 6 to 12-week study designs. 18,38,39 In a recent metaanalysis of 33 weight loss interventions, Selvin et al 43 concluded that there was a strong association between declines in body weight and hs-CRP level, and that weight reduction was an effective non-pharmacological strategy for lowering plasma hs-CRP. This study does not support this finding, as no correlation was found between reduction in hs-CRP and body weight or FM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 and TNF-a are also produced and released from human adipose tissue (18,41), and the circulating levels have been found to be correlated with measures of obesity, insulin resistance and cardiovascular disease in many studies (10,16,19,20,42) but not in all (17,43). Another new finding in the present study was that plasma levels of TNF-a correlated with circulating levels of IL-6 and IL-8, which supports the hypothesis that TNF-a is a leader cytokine inducing the production and release of other cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, Gong et al [19], Roberts et al [20], Rynders et al [21], Izadpanah et al [22], Garanty-Bogacka et al [23], Martos Moreno et al [24], Balagopal et al [25] and Gallistl et al [26] showed similar change in IL-6 levels after decrease of BMI. On the other side, Nemet et al [27], Roth et al [28], and Amati et al [29] found no significant change.…”
Section: Discussionmentioning
confidence: 97%